OPPORTUNITIES AND PROSPECTS OF THE SYSTEM INTEGRATED ASSESSMENT OF IMMUNITY OF CHILDREN SUFFERING ULCER DUODENUM - A. V. Polyanskiy; A. V. Burlutskaya (Кубанский научный медицинский вестник, 2017)
Aim. To explore some regularities of the immune system and resistance in children with ulcer duodenum. On the basis of systemic pathogenetic approach to develop a system of integrated assessment of the immunity of the child with the ulcer duodenum.Materials and methods. A clinical and immunological study of 114 children aged 5-14 years, suffering from an ulcer duodenum. The control group consisted of 30 healthy children of similar age. Investigation of venous blood were performed on the day after admission and after a course of appropriate treatment before discharge. By mathematical analysis of unsubstantiated "factor" structure of the immune system in normal and ulcer duodenum.Results. At different stages of the disease varies the amount and structure of relations between the components within the immune system and its relationship with other systems. Conclusion. These peculiarities – a normal physiological response of the immune system to develop an immunological process in the mucosa of duodenum.